Factors influencing the behavior of bystanders to workplace bullying in healthcare—A qualitative descriptive interview study. Issue 4 (15th April 2022) - Jönsson, Sandra; Muhonen, Tuija
Abstract: Workplace bullying is a severe problem that affects individuals, organizations, and society. Although there is a growing research interest in bystanders of workplace bullying, the rationale underlying bystanders' behavior in healthcare settings requires further investigation. The aim of the current study is to explore factors that influence the behavior of bystanders to workplace bullying in the healthcare sector. Qualitative semistructured interviews were conducted with 32 staff members in the healthcare sector in Sweden. Data were collected between March 2019 and September 2020 and were analyzed with thematic analysis. The participants experienced that bystanders of bullying, both colleagues and managers, were in many situations acting in a passive way. Organizational factors such as dysfunctional organizational culture and deficiencies in management affected how actively the bystanders could intervene. Additionally, a fear of negative consequences, lack of awareness of what was going on, bullying behavior being excused, and the bystander not being a member of the dominant group were social factors contributing to bystanders' passive behavior. For bystander intervention to be successful, the organization must consider bullying as a serious issue, take action, and show support for both the target and the bystander.